2020
DOI: 10.1039/d0nj00282h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and molecular modeling studies of substitutedN-benzyl-2-phenylethanamines as cholinesterase inhibitors

Abstract: 4’-O-methylnorbelladine and other non-natural halogenated protoalkaloids were synthesized by reductive amination. They exerted moderate to good inhibition of cholinesterases which was adequately explained by molecular modeling studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…As it can be seen, the main interactions stabilizing these complexes are with the following amino acid residues: Trp110, Gly144, Thr148, Glu225, Ser226, Trp259, Ser315, Phe357, Asn425, and His466. These interactions have been previously reported by our group for other carbamate derivatives showing butyrylcholinesterase inhibitory activity [67,72]. Notice that interactions that contribute to the BChE complexes formation of the most active ligands are identical to those established by RIV at the active site of BChE.…”
Section: Ser226supporting
confidence: 82%
See 1 more Smart Citation
“…As it can be seen, the main interactions stabilizing these complexes are with the following amino acid residues: Trp110, Gly144, Thr148, Glu225, Ser226, Trp259, Ser315, Phe357, Asn425, and His466. These interactions have been previously reported by our group for other carbamate derivatives showing butyrylcholinesterase inhibitory activity [67,72]. Notice that interactions that contribute to the BChE complexes formation of the most active ligands are identical to those established by RIV at the active site of BChE.…”
Section: Ser226supporting
confidence: 82%
“…This methodology was successfully applied in previous works [60][61][62][63][64][65]. Indeed, we have formerly reported and described the molecular interactions established in the active site of AChE and BChE when complexed with the well-known cholinesterase inhibitors RIV [66,67] and galantamine [68][69][70][71] and other ligands with great structural variability, including alkaloids [69,70], carbamates [67], 4-[(alkoxycarbonyl)amino]benzoates [66], and N-benzyl-2-phenylethanamine derivatives [72].…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%
“…Recently, close derivatives with a norbelladine framework ( N -benzyl-2-phenylethan-1-amine congeners) have been developed by Carmona–Viglianco et al [ 40 ] and screened for their AChE/BuChE potency. The compounds reported herein include the same fundamental unit as compound 1 , but they possess different substitution patterns within the A-ring.…”
Section: Resultsmentioning
confidence: 99%
“…Belladine 1 and norbelladine 2 (firstly extracted from the Amaryllidaceae family [ 1 ]) are bioactive precursors in the synthesis of drugs acting on the central nervous system, such as galantamine 3 , lycorine 4 , and haemanthamine 5 ( Figure 1 , Panel a) [ 2 , 3 ]. They are natural substances emerging in therapy, showing a cholinesterase inhibitory activity comparable to that of 3 in the treatment of Alzheimer’s disease [ 4 , 5 ]. In addition, a computational study suggested that quaternary belladine derivatives can interact with the neuroaminidase (NA) protein of influenza A virus, inhibiting viral release from host cell [ 6 ].…”
Section: Introductionmentioning
confidence: 99%